MYOD1 functions as a clock amplifier as well as a critical co-factor for downstream circadian gene expression in muscle - Hodge, Brian A; Zhang, Xiping; Gutierrez-Monreal, Miguel A; Cao, Yi; Hammers, David W; Yao, Zizhen; Wolff, Christopher A; Du, Ping; Kemler, Denise; Judge, Andrew R; Esser, Karyn A (eLife, 2019)
In the present study we show that the master myogenic regulatory factor, MYOD1, is a positive modulator of molecular clock amplitude and functions with the core clock factors for expression of clock-controlled genes in skeletal muscle. We demonstrate that MYOD1 directly regulates the expression and circadian amplitude of the positive core clock factor Bmal1. We identify a non-canonical E-box element in Bmal1 and demonstrate that is required for full MYOD1-responsiveness. Bimolecular fluorescence complementation assays demonstrate that MYOD1 colocalizes with both BMAL1 and CLOCK throughout myonuclei. We demonstrate that MYOD1 and BMAL1:CLOCK work in a synergistic fashion through a tandem E-box to regulate the expression and amplitude of the muscle specific clock-controlled gene, Titin-cap (Tcap). In conclusion, these findings reveal mechanistic roles for the muscle specific transcription factor MYOD1 in the regulation of molecular clock amplitude as well as synergistic regulation of clock-controlled genes in skeletal muscle.
Keywords: Bmal1; clock; muscle transcription; circadian rhythm